1995
DOI: 10.3109/02770909509083232
|View full text |Cite
|
Sign up to set email alerts
|

Pet Ownership in the UAE: Its Effect on Allergy and Respiratory Symptoms

Abstract: The aim of this paper was to study the effect of pets and other domestic animals on bronchial asthma among United Arab Emirates (UAE) schoolchildren aged 6-14 years. A cross-sectional study of 850 schoolchildren living in both urban and rural areas (average age 9.36 +/- 2.11 years, 46.8% boys and 53.2% girls) was conducted using self-administered questionnaires between October 1992 and May 1993. Prevalence rate for asthma, rhinitis, wheeze, cough, and eczema in children from families with and without animals w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 30 publications
2
6
0
Order By: Relevance
“…Consistent with our findings, a study from Turkey reported that birds were the most commonly kept pets, followed by cats, fish, and dogs (31). A study from the United Arab Emirates (UAE) found the prevalence of any pet-keeping to be 40.7%, similar to our estimate of 42.8% (32). Moreover, the estimate of cat-keeping in our study (13.2%) was similar to that reported by the study conducted in the UAE (14.6%) (32).…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with our findings, a study from Turkey reported that birds were the most commonly kept pets, followed by cats, fish, and dogs (31). A study from the United Arab Emirates (UAE) found the prevalence of any pet-keeping to be 40.7%, similar to our estimate of 42.8% (32). Moreover, the estimate of cat-keeping in our study (13.2%) was similar to that reported by the study conducted in the UAE (14.6%) (32).…”
Section: Discussionsupporting
confidence: 91%
“…5 On the other hand, findings from the European Community Respiratory Health Survey indicate that dog keeping in early childhood protects against adult atopy 6. A study of Swedish children revealed less asthma and allergic rhinitis in children who had a pet during their first year of life 7.…”
mentioning
confidence: 99%
“…The neighboring countries like the UAE have reported on the effect of pet ownership on allergy and respiratory symptoms (Abdulrazzaq, Bener, & DeBuse, 1995;Bener et al, 1993b;Bener, Galadari, & Naser, 1995). The risk of asthma in children with pets at home was found to be twice that of children without (RR = 2.03; 95% CI = 1.40-2.95), compared with our result of (RR = 1.2; 95% CI = 1.1-1.3).…”
Section: Discussionmentioning
confidence: 95%